A randomised clinical trial on a comprehensive geriatric assessment and intensive home follow-up after hospital discharge: the Transitional Care Bridge - de Haan Rob J; van Deelen Bob AJ; Parlevliet Juliette L; Buurman Bianca M; de Rooij Sophia E (BMC, 2010)
Abstract Background Older patients are at high risk for poor outcomes after acute hospital admission. The mortality rate in these patients is approximately 20%, whereas 30% of the survivors decline in their level of activities of daily living (ADL) functioning three months after hospital discharge. Most diseases and geriatric conditions that contribute to poor outcomes could be subject to pro-active intervention; not only during hospitalization, but also after discharge. This paper presents the design of a randomised controlled clinical trial concerning the effect of a pro-active, multi-component, nurse-led transitional care program following patients for six months after hospital admission. Methods/Design Three hospitals in the Netherlands will participate in the multi-centre, double-blind, randomised clinical trial comparing a pro-active multi-component nurse-led transitional care program to usual care after discharge. All patients acutely admitted to the Department of Internal Medicine who are 65 years and older, hospitalised for at least 48 hours and are at risk for functional decline are invited to participate in the study. All patients will receive integrated geriatric care by a geriatric consultation team during hospital admission. Randomization, which will be stratified by study site and cognitive impairment, will be conducted during admission. The intervention group will receive the transitional care bridge program, consisting of a handover moment with a community care Care Nurse (CN) during hospital admission and five home visits after discharge. The control group will receive 'care as usual' after discharge. The main outcome is the level of ADL functioning six months after discharge compared to premorbid functioning measured with the Katz ADL index. Secondary outcomes include; survival, cognitive functioning, quality of life, and health care utilization, satisfaction of the patient and primary care giver with the transitional care bridge program. All outcomes will be measured at three, six and twelve months after discharge. Approximately 674 patients will be enrolled to either the intervention or control group. Discussion The study will provide new knowledge on a combined intervention of integrated care during hospital admission, a proactive handover moment before discharge and intensive home visits after discharge. Trial registration Trial registration number: NTR 2384